2014
DOI: 10.3899/jrheum.140111
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Incident Depression in Systemic Lupus Erythematosus

Abstract: Depression in SLE is multifactorial. Higher-dose prednisone (≥ 20 mg daily) is 1 important independent risk factor. Global disease activity is not a risk factor, but cutaneous activity and certain types of neurologic activity (myelitis) are predictive of depression. The independent effect of prednisone provides clinicians with an additional incentive to avoid and reduce high-dose prednisone exposure in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 42 publications
(75 reference statements)
4
69
2
2
Order By: Relevance
“…Other contributing factors were recent SLE diagnosis, non-Asian ethnicity, cutaneous disease, and longitudinal myelitis. These results may further support the notion that, at least for some patients, SLE related depression is associated with adverse events of therapy rather than with disease activity and may encourage clinicians to reduce prednisone doses or avoid its use [59]. An association of depression and specific antibodies directed at ribosomal-P, NMDA receptor, and other neuronal epitopes have been suggested [9,60].…”
Section: Reviewmentioning
confidence: 53%
See 1 more Smart Citation
“…Other contributing factors were recent SLE diagnosis, non-Asian ethnicity, cutaneous disease, and longitudinal myelitis. These results may further support the notion that, at least for some patients, SLE related depression is associated with adverse events of therapy rather than with disease activity and may encourage clinicians to reduce prednisone doses or avoid its use [59]. An association of depression and specific antibodies directed at ribosomal-P, NMDA receptor, and other neuronal epitopes have been suggested [9,60].…”
Section: Reviewmentioning
confidence: 53%
“…A recent study concluded that depression in SLE is linked to several factors of which the usage of high dose prednisone (20 mg or higher) was found to be the most significant independent factor, while global disease activity was not [59]. Other contributing factors were recent SLE diagnosis, non-Asian ethnicity, cutaneous disease, and longitudinal myelitis.…”
Section: Reviewmentioning
confidence: 99%
“…They are often unrelated to periods of disease activity as conventionally defined (4)(5)(6)(7)(15)(16)(17)(18)(19)(20)(21) and usually do not respond to therapy with immunosuppression or corticosteroids, even with escalation of doses. Such symptoms tend to be chronic.…”
Section: Type 2 Manifestationsmentioning
confidence: 99%
“…Further, among individuals with RA, most depressive disorders developed within five years after RA diagnosis [151]. When examining a cohort of 1,609 individuals with no prior history of depression and SLE, it was found that incidence of depression was as high as 29.7 episodes per 1000 person-years [152]. …”
Section: Incident Depression and Arthritismentioning
confidence: 99%